Sodium dithionite‑enhanced quality of radix scutellariae through modification of secondary metabolism - Huimin, Guo; Xiaoying, Fu; Hongwei, Du; Wei, Cong; Xiangcai, Meng (International Journal of Pharmaceutical Investigation)
Introduction: The quality of radix scutellariae is particularly associated with environmental stresses, but detailed mechanisms remained unclear. Plant under unfavorable situation generates redundant reactive oxygen species (ROS), and ROS can modify the secondary metabolism. The varied quality of radix scutellariae could be explained by ROS. Materials and Methods: 0.004, 0.4, and 40 µmol/L of sodium dithionite (Na2S2O4), a material producing ROS, were applied to Scutellaria baicalensis to mimic unfavorable situation. The relationship between ROS, antioxidant enzymes activity, and secondary metabolite was investigated. Results: ROS level fails to rise due to both the antioxidase and the secondary metabolites. The activities of both superoxide dismutase and catalase in the roots of S. baicalensis showed a moderately improvement, meanwhile the phenylalanine ammonia lyase was strongly expressed, and the biosynthesis of flavonoids was heavily elevated. Although the glycosides such as baicalin and wogonoside changed little, the aglycones with the highest effective, such as baicalein and wogonin, were increased by approximately 50%–100%. Conclusion: This is very valuable in insight into the stress physiology and provides a strong tool to enhance the quality of radix scutellariae.
Keywords: Antioxidase; flavonoids; reactive oxygen species; Scutellaria baicalensis; secondary metabolite